APLIKASI TEKNOLOGI PENGADAAN AIR BERSIH DI EMPAT DESA TERTINGGAL DI BENGKULU SELATAN - Rahardjo, Petrus Nugro (Center for Environmental Technology, 2007)
In County South Bengkulu there are 4 villages classified into poor villages. Those villages do not have some principal facilities yet, such as clean water supply system and electricity. To fulfill clean water need, the people use shallow groundwater which has very bad quality. The groundwater contains Fe (1.7 ppm) and Mn (0.7 ppm). The contents are much more than the standard quality allowed by WHO. The groundwater colour is also a little bit brown. To deal with those problems, BPPT (Agency for the Assessment and Application of Technology) has tried to apply a water treatment system which is supported by a solar cell system producing the electricity. The electric energy is used for pumping the groundwater. The water treatment has a mainly important process which is accommodated in a multy media filter. The media include coarse coral, find coral, sand silica, manganese zeolite and activated carbon. The media filter can reduce the contaminants (Fe & Mn) and remove the odour effectively. The complete water treatment system has been applied successfully in the 4 villages (one for each village). Ã‚Â Ã‚Â Ã‚Â Keywords : Clean Water Supply Technology.